Study of the Chemical Changes and Evolution of Microbiota During Sourdoughlike Fermentation of Wheat Bran. Issue 4 (23rd July 2014) - Manini, Federica; Brasca, Milena; Plumed‐Ferrer, Carme; Morandi, Stefano; Erba, Daniela; Casiraghi, Maria Cristina
ABSTRACT: Several studies have emphasized the possibility of enhancing nutritional properties of cereal by‐products through biotechnological processes. Bran fermentation positively affects the bioavailability of several functional compounds. Moreover, bran fermentation could increase water‐extractable arabinoxylans (WEAX), compounds with positive effects on glucose metabolism and prebiotic properties. This study was aimed at increasing the amount of bran bioactive compounds through a sourdoughlike fermentation process. Wheat bran fermentations were conducted through continuous propagation by back‐slopping of fermented bran (10% inoculum) until a stable microbiota was established, reaching high counts of lactic acid bacteria and yeasts (10 9 and 10 7 CFU/g, respectively). At each refreshment step, bacterial strains were isolated, clustered, molecularly analyzed by randomly amplified polymorphic DNA, and identified at the species level by 16S rRNA gene sequencing. Leuconostoc mesenteroides, Lactobacillus brevis, Lactobacillus curvatus, Lactobacillus sakei, Lactobacillus plantarum, Pediococcus pentosaceus, and Pichia fermentans dominated the stable sourdough ecosystem. After fermentation, levels of soluble fiber increased (+30%), and WEAX and free ferulic acid were respectively fourfold and tenfold higher than in raw bran, results probably related to microbial xylan‐degrading activity, whereas phytic acid was completely degraded. These preliminary data suggest that fermented bran could be considered an interesting functional ingredient for nutritional enhancement.